Effect of Low Dose Azithromycin Towards The Long Period of Clinical Improvement, Level of IL-8 And Sputum Neutrophil of Pneumonia Patients - Leonardo H. Simandjuntak; Reviono Reviono; Harsini Harsini (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Backgrounds: Pneumonia is an acute inflammation of the lung parenchyma caused by microorganisms. Inflammation is an immune response that occurs when bacterial infection. The immune response that occurs will induce alveolar macrophages secrete IL-8 which mediates the movement of neutrophils into the alveolar to release reactive oxygen species (ROS) and protease. Low-dose azithromycin has anti-inflammatory effects that are used on a chronic inflammatory disease of the lung, so its use in pneumonia interesting to do. This study aimed to determine the effect of low-dose azithromycin towards the long period of clinical improvement, level of IL-8 and sputum neutrophil of pneumonia patients. Methode: This research is an experimental study with pretest and post-test design. Subjects were patients with pneumonia who were treated at the Hospital Dr. Moewardi Surakarta in July - August 2016. Samples were taken by consecutive sampling as many as 30 patients. treatment group (n = 15) received additional therapy of azithromycin 250 mg / day and the control group (n = 15) received additional placebo. Result: Supplementation of low-dose azithromycin was significantly reduced levels of IL-8 (reduction = -90.31 ± 89.30; P=0.002) and sputum neutrophil (reduction = -35.73 ± 25.25; P=0.0001) in pneumonia patients. There is a statistically significant difference (P=0.0001) of the long period of clinical improvement between treatment groups (3.87 + 0.64 days) and control (5,60+ 0.91 days). Conclusion: Supplementation 250 mg/day of azithromycin during hospitalization led to decreased levels of IL-8 serum, sputum neutrophil, and affect the long period of clinical improvement in pneumonia patients. (J Respir Indo 2018; 38(1): 39-47)